Solution‐Processable Van Der Waals Heterojunctions on Silicon for Self‐Powered Photodetectors with High Responsivity and Detectivity - Yuansheng Ge; Da Lei; Chaojun Zhang; Quan Zhang; Jinlong Mu; Jing Li (Advanced Science)
Abstract The high density of surface states on silicon has long impeded the development of high‐performance photodetectors, leading to excessive dark leakage currents that adversely affect responsivity and detectivity. Herein, an all‐solution‐processable method is presented for fabricating photodetectors through consecutive spray‐coating of a conductive metal‐organic framework (MOF, Cu3(HHTP)2) and metallic Ti3C2 MXene to form van der Waals dual junctions on a silicon substrate. The heterojunction configuration facilitates unidirectional electron‐hole separation within the Cu3(HHTP)2/Si interface with type I band alignment, while leveraging the potential barrier difference between the Cu3(HHTP)2/Si and Ti3C2/Cu3(HHTP)2 Schottky junctions. The Ti3C2/Cu3(HHTP)2/Si photodetector demonstrates outstanding photoelectric performance, operating in a self‐powered mode with a high specific detectivity of 1.63 × 1012 Jones and a large responsivity of 1.8 A W−1 under 365 nm illumination. It also exhibits an impressive on/off ratio exceeding 3.9 × 104 at an incident light power density of 330 µW cm−2. Additionally, the photodetector maintains excellent responsivity across a broad wavelength range from 365 to 700 nm, spanning ultraviolet to visible light, and sets a new performance benchmark for MOF‐based photodetectors. This work introduces a straightforward, controllable approach for constructing high‐quality van der Waals junctions on semiconductor surfaces, enabling the fabrication of optoelectronic devices with enhanced performance.